Isolation of Candidatus Bartonella rousetti and Other Bat-associated Bartonellae from Bats and Their Flies in Zambia - Qiu, Yongjin (Pathogens, 2020)
Bat-associated bartonellae, including Bartonella mayotimonensis and Candidatus Bartonella rousetti, were recently identified as emerging and potential zoonotic agents, respectively. However, there is no report of bat-associated bartonellae in Zambia. Thus, we aimed to isolate and characterize Bartonella spp. from bats and bat flies captured in Zambia by culturing and PCR. Overall, Bartonella spp. were isolated from six out of 36 bats (16.7%), while Bartonella DNA was detected in nine out of 19 bat flies (47.3%). Subsequent characterization using a sequence of five different genes revealed that three isolates obtained from Egyptian fruit bats (Rousettus aegyptiacus) were Ca. B. rousetti. The isolates obtained from insectivorous bats (Macronycteris vittatus) were divided into two previously unclassified bat-associated bartonellae. A phylogenetic analysis of the six genotypes of Bartonella gltA sequences from nine pathogen-positive bat flies revealed that three genotypes belonged to the same clades as bat-associated bartonellae, including Ca. B. rousetti. The other three genotypes represented arthropod-associated bartonellae, which have previously been isolated only from ectoparasites. We demonstrated that Ca. B. rousetti is maintained between bats (R. aegyptiacus) and bat flies in Zambia. Continuous surveillance of Bartonella spp. in bats and serological surveys in humans in Africa are warranted to evaluate the public health importance of bat-associated bartonellae.